Necessary or oversimplification? On the strengths and limitations of current assessments to integrate social dimensions in planetary boundaries - Lukas Drees; Robert Luetkemeier; Heide Kerber (Ecological Indicators, 2021)
With the Earth system being about to leave Holocene conditions and thus the known safe operating space for humanity, frameworks such as the Planetary Boundaries (PBs) and the Sustainable Development Goals (SDGs) provide quantitative metrics to guide sustainability transformations. In order to strive, not only for compliance with the PBs but also for societal well-being, some approaches attempt to combine both PBs and SDGs within a single assessment.We focus on two prominent examples, the “Doughnut” by Kate Raworth and the #SDGinPB project of the 2018 report to the Club of Rome, which are not only aimed at public outreach, but also at guiding policy-making. To meet these objectives, the approaches should possess a certain accuracy in determining the progress in achieving the SDGs and in complying with the PBs. We evaluate, by using a multi-indicator approach for comparison, whether both approaches’ limited set of indicators can still represent the SDGs’ complexity. This comparative approach estimates the progress in achieving SDGs, especially in the Global North, to be significantly lower.Based on these results and against the approaches’ purposes, we discuss their simplifications and at which point the results are no longer reliable. We conclude that global assessments can be an important factor in initiating transformative processes by stimulating public discourse, but that the actual implementation of these would require approaches with greater recognition of local particularities.